1ISG-009 Economic impact of aflibercept optimisation for the treatment of eye-related conditions - Garciadeparedes-Esteban, JC (Eur J Hosp Pharm, 2018)
BACKGROUND: Aflibercept is indicated for adults in the treatment of neovascular (wet) age-related macular degeneration (AMD) and visual impairment due to macular oedema secondary to retinal vein occlusion (RVO), diabetic macular oedema (DME) or myopic choroidal neovascularisation (CNV). PURPOSE: To describe the indications and the cost savings achieved from prepared aflibercept intravitreal syringes in patients with the above-mentioned ophthalmic conditions. MATERIAL AND METHODS: A protocol was implemented, in collaboration with the ophthalmology service, which consists of grouping the patients receiving treatment with aflibercept and fractionating the vial in intravitreal syringes to adjust to the recommended dose of 2 mg according to the summary of product characteristics. The hospital pharmacy department prepares 2 mg/0.05 mL sterile intravitreal aflibercept syringes from 4 mg/0.1 mL commercial vials in a horizontal laminar flow hood. The vials contain a surplus and from each vial, three syringes are obtained. A retrospective study was conducted which included patients receiving at least one dose of intravitreal aflibercept from January 2016 to June 2017. The variables studied were: sex, age, indications, average number of administrations per patient and the total number of intravitreal syringes. Direct costs between the use of aflibercept syringes instead of vials were compared in order to calculate the economic saving. RESULTS: During the study period, 265 patients were included, of which 142 were males with a median age of 74±11 years. Of the total number of patients, 110 patients were diagnosed with AMD, 89 with DME, 45 with RVO and 21 with CNV. The average number of administrations per patient was four. Each vial cost €612.31 and therefore each syringe cost €204.10. A total of 1149 intravitreal syringes were administered and this meant a total cost of €234,510.90. If the corresponding number of vials had been used, the total cost would have been €703,544.19. The total savings were €469,033.29. CONCLUSION: The pathology leading to increased expenditure on aflibercept was AMD, followed by DME which accounted for around 75% of expenditure. The optimisation of the vials of aflibercept represents an important economic saving. It is important to group the patients three at a time so as not to miss the optimisation. No conflict of interest